Local Wisdom in the Collection of Flying Fish Eggs (Hirundicticthys oxycephalus) (Case Study of Patorani Fishermen in Pa'lalakkang Village, North Galesong District, Takalar Regency, South Sulawesi Province) - Talitha Wenifrida Massenga (Budapest International Research and Critics University, 2022)
Patorani fishermen are the community living on the coast of Pa'lalakang Village, North Galesong District, Takalar Regency, South Sulawesi Province. Their main livelihood is to collect flying fish eggs (Hirundicticthys oxycephalus) which in the process of catching still apply local wisdom, namely norms that must be obeyed, and become an unwritten law in the process of catching flying fish eggs. Patorani as a local community was able to combine modern technology with traditional knowledge. Traditional knowledge used is erang passimombalang and erang pakboya-boyang, while modern technology (motorboat) used is only as a tool to facilitate work. Local wisdom (traditional knowledge) in addition to teach the relationship between humans and their creators, also teaches how humans relate to their natural environment. The manifestation of this knowledge was that Patorani changed their fishing gear from pakkaja to balla-balla, along with the transition from the main commodity, namely from fish to eggs. If they use pakkaja fishing, the flying fish (Torani) will also get caught, but when they use balla-balla, the flying fish will not get caught. Thus, the exploitation of marine resources can be minimized.